Testing bacterial and fungal isolates for biological control of Fusarium culmorum - Boyd-Wilson, K.S.H.; Magee, L.J.; Hackett, J.K.; Walter, M. (New Zealand Plant Protection, 2000)
Microorganisms isolated from composts were assayed in vitro for inhibition of mycelial growth and conidium germination of Fusarium culmorum Eleven bacterial isolates inhibited mycelial growth and of these seven also inhibited germination of conidia However inhibition of mycelial growth was only reproducible for three bacteria Five fungal isolates were found to have antagonistic effects on F culmorum mycelial growth Of these five three isolates gave reproducible results and also suppressed germination of F culmorum conidia An oat seedling bioassay was developed to determine the potential of microbial antagonists for use as seed treatments against F culmorum in soil inoculated with the pathogen Three bacterial isolates were selected for methodology development for in vivo evaluations The effect of F culmorum inoculation technique growth substrate and assessment method were investigated